Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 631679 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Elops Linnaeus, 1766", "TaxonKey is Hypomesus Gill, 1862", "TaxonKey is Catostomus Lesueur, 1817", "TaxonKey is Anguilla Schrank, 1798", "TaxonKey is Hilsa Regan, 1917", "TaxonKey is Gasterosteus Linnaeus, 1758", "TaxonKey is Lampetra Bonnaterre, 1788", "TaxonKey is Lates Cuvier, 1828", "TaxonKey is Chelone Brongniart, 1805", "TaxonKey is Citharinus Cuvier, 1816", "TaxonKey is Brachymystax Günther, 1866", "TaxonKey is Clupeonella Kessler, 1877", "TaxonKey is Liza", "TaxonKey is Chelonodon Müller, 1841", "TaxonKey is Ethmalosa Regan, 1917", "TaxonKey is Microphis Hallowell, 1854", "TaxonKey is Aldrichetta Whitley, 1945", "TaxonKey is Agonostomus Bennett, 1832", "TaxonKey is Lateolabrax Bleeker, 1855", "TaxonKey is Gymnothorax Bloch, 1795", "TaxonKey is Huso Brandt & Ratzeburg, 1833", "TaxonKey is Acipenser Linnaeus, 1758", "TaxonKey is Caspiomyzon Berg, 1906", "TaxonKey is Atherinosoma Castelnau, 1872", "TaxonKey is Ilisha Richardson, 1846", "TaxonKey is Lycengraulis Günther, 1868", "TaxonKey is Cichlasoma Swainson, 1839", "TaxonKey is Galaxias Cuvier, 1816", "TaxonKey is Brachirus Swainson, 1838", "TaxonKey is Coilia Gray, 1830", "TaxonKey is Alosa Linck, 1790", "TaxonKey is Clarotes Kner, 1855", "TaxonKey is Cottus Linnaeus, 1758", "TaxonKey is Lovettia McCulloch, 1915", "TaxonKey is Microgadus Gill, 1865", "TaxonKey is Kuhlia Gill, 1861", "TaxonKey is Anchoviella Fowler, 1911", "TaxonKey is Dorosoma Rafinesque, 1820", "TaxonKey is Herklotsichthys Whitley, 1951", "TaxonKey is Ellochelon Whitley, 1930", "TaxonKey is Lutjanus Bloch, 1790", "TaxonKey is Hucho Günther, 1866", "TaxonKey is Geotria Gray, 1851", "TaxonKey is Joturus Poey, 1860", "TaxonKey is Crenimugil Schultz, 1946", "TaxonKey is Lethenteron Creaser & Hubbs, 1922", "TaxonKey is Coregonus Linnaeus, 1758", "TaxonKey is Entosphenus Gill, 1862" ] } The dataset includes 631679 records from 549 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003936-150811131857512/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences